Pengaruh Perencanaan Pajak dan Struktur Modal terhadap Nilai Perusahaan dengan Ukuran Perusahaan sebagai Pemoderasi - Novianti Novianti; Lodang Prananta Widya Sasana (Akuntansi dan Ekonomi Pajak: Perspektif Global, 2026)
This study aims to determine the effect of tax planning and capital structure on firm value, with firm size as a moderator. The population in this study is all non-cyclical consumer companies in the food and beverage subsector listed on the Indonesia Stock Exchange (IDX) for the 2020-2024 period. The type of research used in this study is quantitative associative with secondary data. The research sample was determined using a purposive sampling technique. Based on this technique, 24 companies were obtained that met certain criteria. The panel data regression technique used in this study is the Random Effect Model. Testing of panel data regression and moderation regression uses the E=views 13 application. The results of this study indicate that tax planning partially has no effect on firm value, while capital structure does affect firm value. The results simultaneously show that tax planning and capital structure affect firm value. The results of this study also indicate that firm size weakens the relationship between tax planning and firm value, and firm size is also unable to moderate or weaken the relationship between capital structure and firm value.